Jump to content
Wikipedia The Free Encyclopedia

Darboux's theorem (analysis)

From Wikipedia, the free encyclopedia
All derivatives have the intermediate value property

In mathematics, Darboux's theorem is a theorem in real analysis, named after Jean Gaston Darboux. It states that every function that results from the differentiation of another function has the intermediate value property: the image of an interval is also an interval.

When ƒ is continuously differentiable (ƒ in C1([a,b])), this is a consequence of the intermediate value theorem. But even when ƒ′ is not continuous, Darboux's theorem places a severe restriction on what it can be.

Darboux's theorem

[edit ]

Let I {\displaystyle I} {\displaystyle I} be a closed interval, f : I R {\displaystyle f\colon I\to \mathbb {R} } {\displaystyle f\colon I\to \mathbb {R} } be a real-valued differentiable function. Then f {\displaystyle f'} {\displaystyle f'} has the intermediate value property: If a {\displaystyle a} {\displaystyle a} and b {\displaystyle b} {\displaystyle b} are points in I {\displaystyle I} {\displaystyle I} with a < b {\displaystyle a<b} {\displaystyle a<b}, then for every y {\displaystyle y} {\displaystyle y} between f ( a ) {\displaystyle f'(a)} {\displaystyle f'(a)} and f ( b ) {\displaystyle f'(b)} {\displaystyle f'(b)}, there exists an x {\displaystyle x} {\displaystyle x} in [ a , b ] {\displaystyle [a,b]} {\displaystyle [a,b]} such that f ( x ) = y {\displaystyle f'(x)=y} {\displaystyle f'(x)=y}.[1] [2] [3]

Proofs

[edit ]

Proof 1. The first proof is based on the extreme value theorem.

If y {\displaystyle y} {\displaystyle y} equals f ( a ) {\displaystyle f'(a)} {\displaystyle f'(a)} or f ( b ) {\displaystyle f'(b)} {\displaystyle f'(b)}, then setting x {\displaystyle x} {\displaystyle x} equal to a {\displaystyle a} {\displaystyle a} or b {\displaystyle b} {\displaystyle b}, respectively, gives the desired result. Now assume that y {\displaystyle y} {\displaystyle y} is strictly between f ( a ) {\displaystyle f'(a)} {\displaystyle f'(a)} and f ( b ) {\displaystyle f'(b)} {\displaystyle f'(b)}, and in particular that f ( a ) > y > f ( b ) {\displaystyle f'(a)>y>f'(b)} {\displaystyle f'(a)>y>f'(b)}. Let φ : I R {\displaystyle \varphi \colon I\to \mathbb {R} } {\displaystyle \varphi \colon I\to \mathbb {R} } such that φ ( t ) = f ( t ) y t {\displaystyle \varphi (t)=f(t)-yt} {\displaystyle \varphi (t)=f(t)-yt}. If it is the case that f ( a ) < y < f ( b ) {\displaystyle f'(a)<y<f'(b)} {\displaystyle f'(a)<y<f'(b)} we adjust our below proof, instead asserting that φ {\displaystyle \varphi } {\displaystyle \varphi } has its minimum on [ a , b ] {\displaystyle [a,b]} {\displaystyle [a,b]}.

Since φ {\displaystyle \varphi } {\displaystyle \varphi } is continuous on the closed interval [ a , b ] {\displaystyle [a,b]} {\displaystyle [a,b]}, the maximum value of φ {\displaystyle \varphi } {\displaystyle \varphi } on [ a , b ] {\displaystyle [a,b]} {\displaystyle [a,b]} is attained at some point in [ a , b ] {\displaystyle [a,b]} {\displaystyle [a,b]}, according to the extreme value theorem.

Because φ ( a ) = f ( a ) y > 0 {\displaystyle \varphi '(a)=f'(a)-y>0} {\displaystyle \varphi '(a)=f'(a)-y>0}, we know φ {\displaystyle \varphi } {\displaystyle \varphi } cannot attain its maximum value at a {\displaystyle a} {\displaystyle a}. (If it did, then ( φ ( t ) φ ( a ) ) / ( t a ) 0 {\displaystyle (\varphi (t)-\varphi (a))/(t-a)\leq 0} {\displaystyle (\varphi (t)-\varphi (a))/(t-a)\leq 0} for all t ( a , b ] {\displaystyle t\in (a,b]} {\displaystyle t\in (a,b]}, which implies φ ( a ) 0 {\displaystyle \varphi '(a)\leq 0} {\displaystyle \varphi '(a)\leq 0}.)

Likewise, because φ ( b ) = f ( b ) y < 0 {\displaystyle \varphi '(b)=f'(b)-y<0} {\displaystyle \varphi '(b)=f'(b)-y<0}, we know φ {\displaystyle \varphi } {\displaystyle \varphi } cannot attain its maximum value at b {\displaystyle b} {\displaystyle b}.

Therefore, φ {\displaystyle \varphi } {\displaystyle \varphi } must attain its maximum value at some point x ( a , b ) {\displaystyle x\in (a,b)} {\displaystyle x\in (a,b)}. Hence, by Fermat's theorem, φ ( x ) = 0 {\displaystyle \varphi '(x)=0} {\displaystyle \varphi '(x)=0}, i.e. f ( x ) = y {\displaystyle f'(x)=y} {\displaystyle f'(x)=y}.

Proof 2. The second proof is based on combining the mean value theorem and the intermediate value theorem.[1] [2]

Define c = 1 2 ( a + b ) {\displaystyle c={\frac {1}{2}}(a+b)} {\displaystyle c={\frac {1}{2}}(a+b)}. For a t c , {\displaystyle a\leq t\leq c,} {\displaystyle a\leq t\leq c,} define α ( t ) = a {\displaystyle \alpha (t)=a} {\displaystyle \alpha (t)=a} and β ( t ) = 2 t a {\displaystyle \beta (t)=2t-a} {\displaystyle \beta (t)=2t-a}. And for c t b , {\displaystyle c\leq t\leq b,} {\displaystyle c\leq t\leq b,} define α ( t ) = 2 t b {\displaystyle \alpha (t)=2t-b} {\displaystyle \alpha (t)=2t-b} and β ( t ) = b {\displaystyle \beta (t)=b} {\displaystyle \beta (t)=b}.

Thus, for t ( a , b ) {\displaystyle t\in (a,b)} {\displaystyle t\in (a,b)} we have a α ( t ) < β ( t ) b {\displaystyle a\leq \alpha (t)<\beta (t)\leq b} {\displaystyle a\leq \alpha (t)<\beta (t)\leq b}. Now, define g ( t ) = ( f β ) ( t ) ( f α ) ( t ) β ( t ) α ( t ) {\displaystyle g(t)={\frac {(f\circ \beta )(t)-(f\circ \alpha )(t)}{\beta (t)-\alpha (t)}}} {\displaystyle g(t)={\frac {(f\circ \beta )(t)-(f\circ \alpha )(t)}{\beta (t)-\alpha (t)}}} with a < t < b {\displaystyle a<t<b} {\displaystyle a<t<b}. g {\displaystyle ,円g} {\displaystyle ,円g} is continuous in ( a , b ) {\displaystyle (a,b)} {\displaystyle (a,b)}.

Furthermore, g ( t ) f ( a ) {\displaystyle g(t)\rightarrow {f}'(a)} {\displaystyle g(t)\rightarrow {f}'(a)} when t a {\displaystyle t\rightarrow a} {\displaystyle t\rightarrow a} and g ( t ) f ( b ) {\displaystyle g(t)\rightarrow {f}'(b)} {\displaystyle g(t)\rightarrow {f}'(b)} when t b {\displaystyle t\rightarrow b} {\displaystyle t\rightarrow b}; therefore, from the Intermediate Value Theorem, if y ( f ( a ) , f ( b ) ) {\displaystyle y\in ({f}'(a),{f}'(b))} {\displaystyle y\in ({f}'(a),{f}'(b))} then, there exists t 0 ( a , b ) {\displaystyle t_{0}\in (a,b)} {\displaystyle t_{0}\in (a,b)} such that g ( t 0 ) = y {\displaystyle g(t_{0})=y} {\displaystyle g(t_{0})=y}. Let's fix t 0 {\displaystyle t_{0}} {\displaystyle t_{0}}.

From the Mean Value Theorem, there exists a point x ( α ( t 0 ) , β ( t 0 ) ) {\displaystyle x\in (\alpha (t_{0}),\beta (t_{0}))} {\displaystyle x\in (\alpha (t_{0}),\beta (t_{0}))} such that f ( x ) = g ( t 0 ) {\displaystyle {f}'(x)=g(t_{0})} {\displaystyle {f}'(x)=g(t_{0})}. Hence, f ( x ) = y {\displaystyle {f}'(x)=y} {\displaystyle {f}'(x)=y}.

Darboux function

[edit ]

A Darboux function is a real-valued function ƒ which has the "intermediate value property": for any two values a and b in the domain of ƒ, and any y between ƒ(a) and ƒ(b), there is some c between a and b with ƒ(c) = y.[4] By the intermediate value theorem, every continuous function on a real interval is a Darboux function. Darboux's contribution was to show that there are discontinuous Darboux functions.

Every discontinuity of a Darboux function is essential, that is, at any point of discontinuity, at least one of the left hand and right hand limits does not exist.

An example of a Darboux function that is discontinuous at one point is the topologist's sine curve function:

x { sin ( 1 / x ) for  x 0 , 0 for  x = 0. {\displaystyle x\mapsto {\begin{cases}\sin(1/x)&{\text{for }}x\neq 0,\0円&{\text{for }}x=0.\end{cases}}} {\displaystyle x\mapsto {\begin{cases}\sin(1/x)&{\text{for }}x\neq 0,\0円&{\text{for }}x=0.\end{cases}}}

By Darboux's theorem, the derivative of any differentiable function is a Darboux function. In particular, the derivative of the function x x 2 sin ( 1 / x ) {\displaystyle x\mapsto x^{2}\sin(1/x)} {\displaystyle x\mapsto x^{2}\sin(1/x)} is a Darboux function even though it is not continuous at one point.

An example of a Darboux function that is nowhere continuous is the Conway base 13 function.

Darboux functions are a quite general class of functions. It turns out that any real-valued function ƒ on the real line can be written as the sum of two Darboux functions.[5] This implies in particular that the class of Darboux functions is not closed under addition.

A strongly Darboux function is one for which the image of every (non-empty) open interval is the whole real line. [4]

Notes

[edit ]
  1. ^ a b Apostol, Tom M.: Mathematical Analysis: A Modern Approach to Advanced Calculus, 2nd edition, Addison-Wesley Longman, Inc. (1974), page 112.
  2. ^ a b Olsen, Lars: A New Proof of Darboux's Theorem, Vol. 111, No. 8 (Oct., 2004) (pp. 713–715), The American Mathematical Monthly
  3. ^ Rudin, Walter: Principles of Mathematical Analysis, 3rd edition, MacGraw-Hill, Inc. (1976), page 108
  4. ^ a b Ciesielski, Krzysztof (1997). Set theory for the working mathematician. London Mathematical Society Student Texts. Vol. 39. Cambridge: Cambridge University Press. pp. 106–111. ISBN 0-521-59441-3. Zbl 0938.03067.
  5. ^ Bruckner, Andrew M: Differentiation of real functions, 2 ed, page 6, American Mathematical Society, 1994
[edit ]

AltStyle によって変換されたページ (->オリジナル) /